Separation of 1,3-Dimethylamylamine (1,3-DMAA) Stereoisomers, a Stimulant Drug, by Liquid Chromatography - Maria de Almeida Mexia de Almeida; Virgínia M. Gonçalves; Alexandra S. Maia; Diana Dias da Silva; Ricardo Jorge Dinis-Oliveira; Cláudia Ribeiro (RevSALUS)
Background: 1,3-Dimethylamylamine (1,3-DMAA), also known as methylhexanamine, is a central nervous system stimulant with structural similarities with amphetamines and, therefore, presenting overlapping biological and detrimental effects [1]. Despite being banned, the presence of 1,3-DMAA in doping controls and dietary supplements continues to be of significant concern. This molecule has two stereogenic centres and, thus, four stereoisomers [2]. It is widely recognized that enantiomers may exhibit different biological activities, including pharmacokinetics, pharmacodynamics, and toxicity. Consequently, developing analytical methods for enantioselective separation of 1,3-DMAA is crucial to isolate and accurately determine the risks associated with each of these stereoisomers. Objective: To develop a semipreparative liquid chromatography with diode array detection (LC-DAD) method for separating the stereoisomers of 1,3-DMAA. Methods: For that, 1,3-DMAA was derivatized using the enantiomeric pure reagent (R)-(-)-α-methoxy-α-(trifluoromethyl)phenylacetyl chloride ((R)-MTPA-Cl) for the formation of diastereomers. Subsequently, the solution was evaporated, reconstituted in acetonitrile or mobile phase (under testing) or 0.1% formic acid, and analyzed by LC-DAD. Different conventional and chiral analytical columns and chromatographic conditions were tested depending on the column used. Seventy-two tests were carried out with 6 different columns and under different conditions. Results: Preliminary results showed that the derivatization procedure allowed the formation of four 1,3-DMAA diastereomers confirmed by gas chromatography. In liquid chromatography tests, the running conditions were optimized, and the best conditions allowed the separation of two pairs of diastereomers. For the Luna 3µm PFP column, the best eluents were ultrapure water and methanol, both with 0.1% formic acid, with a gradient elution; for the Lux® 3µm Amylose-1 column the best eluents were hexane and isopropanol, both with 0.1% diethylamine by isocratic elution; for the RP-18 LiChrospher® column, the best eluents were ultrapure water, methanol and acetonitrile, all with 0.1% formic acid, by gradient elution. Conclusions: Chromatographic conditions for enantioselective separation of the two stereoisomers of 1,3-DMAA by LC-DAD have been optimized. The isolation of each stereoisomer is crucial for assessing the differential pharmacokinetics and pharmacodynamics and, consequently, to unveil the perils associated with their presence in food supplement and biological samples.